The enduring importance of parenting: caregiving quality and fear-potentiated startle in emerging adults with a child maltreatment history - Sullivan, Alexandra D. W. (Child maltreatment, 2023)
Background: The transition to adulthood is a period of increased risk for emergent psychopathology; emerging adults with a childhood maltreatment history are at risk for poor outcomes. Method: Using a multi-measure, transdisciplinary, cross-sectional design, this study tested whether participant-reported positive parenting, a potential resilience-promoting factor, moderated the association between clinician-rated PTSD symptom severity and a transdiagnostic maladjustment biomarker, fear-potentiated startle (FPS), in a sample of 66 emerging adults (Myears = 18.83, SD = 0.89) with a maltreatment history. We hypothesized that characteristics of effective parenting would moderate the relation between PTSD symptoms and FPS. Results: Results indicated that elevated PTSD, as measured by the CAPS, was associated with a more severe startle reaction. The magnitude of the increase in startle reactivity was moderated by parenting such that those with more positive parenting (Accepting [relative to rejecting]: b = ?0.42, p < .001; Psychologically-controlling [relative to autonomy-promoting]: b = 2.96, p = .004) had significantly less reactivity across the task at higher levels of PTSD symptoms. Conclusions: Emerging adults with childhood maltreatment histories, high levels of PTSD symptoms, and who perceive present-day high-quality caregiver support may cope better with novel stressors relative to youth lacking that support, potentially translating to better psychological outcomes.